Changed gene expression in subjects with schizophrenia and low cortical muscarinic M1 receptors predicts disrupted upstream pathways interacting with that receptor - Scarr, E (Mol Psychiatry, 2018)
We tested the hypothesis that, compared with subjects with no history of psychiatric illness (controls), changes in gene expression in the dorsolateral prefrontal cortex from two subgroups of subjects with schizophrenia, one with a marked deficit in muscarinic M1 receptors (muscarinic receptor-deficit schizophrenia (MRDS)), would identify different biochemical pathways that would be affected by their aetiologies. Hence, we measured levels of cortical (Brodmann area 9) mRNA in 15 MRDS subjects, 15 subjects with schizophrenia but without a deficit in muscarinic M1 receptors (non-MRDS) and 15 controls using Affymetrix Exon 1.0 ST arrays. Levels of mRNA for 65 genes were significantly different in the cortex of subjects with MRDS and predicted changes in pathways involved in cellular movement and cell-to-cell signalling. Levels of mRNA for 45 genes were significantly different in non-MRDS and predicted changes in pathways involved in cellular growth and proliferation as well as cellular function and maintenance. Changes in gene expression also predicted effects on pathways involved in amino acid metabolism, molecular transport and small-molecule biochemistry in both MRDS and non-MRDS. Overall, our data argue a prominent role for glial function in MRDS and neurodevelopment in non-MRDS. Finally, the interactions of gene with altered levels of mRNA in the cortex of subjects with MRDS suggest many of their affects will be upstream of the muscarinic M1 receptor. Our study gives new insight into the molecular pathways affected in the cortex of subjects with MRDS and supports the notion that studying subgroups within the syndrome of schizophrenia is worthwhile.